“SMART CITY” & BRIGHT AND OPAQUE TERRITORIES IN SALVADOR - Santos, Luis Claudio Rios; de Carvalho, Silvana Sá (Seven Editora, 2025)
This study sought to analyze, in light of Milton Santos' contributions, how technologies can contribute to the knowledge of the geographic dynamics of the city of Salvador-BA and its Opaque Territories, targets for investment through the construction of public policies based on the use of Information and Communication Technologies - ICTs. It also sought to reflect on how these technologies can contribute to the territorialization of cities that decide to enter the transformation process toward the condition of a “Smart City”.DOI: https://doi.org/10.56238/sevened2024.037-199